O precedente na fundamentação da decisão judicial - Carvalho, Ricardo José Ramos de (2012)
Besides demonstrating the importance and normative force of the precedents currently present in national law, this study prepares a critical analysis of the overuse of precedent on the grounds of judgment. Beyond that, as revealed in most cases, is the contempt in which many judges have held the legal argument and when issuing their judgment they replace argumentative reasoning by emendated of appellate court decision. First, however, other issues will be addressed showing that recent procedural changes have contributed decisively to the development of the above cited trend. In the initial research themes will be observed and analyzed showing that the contemporary juridical scenario serves to provide input for the core development of the research